Characterization and physical properties of electrospun gelatin nanofibrous films by incorporation of nano-hydroxyapatite. (June 2020) - Deng, Lingli; Li, Yang; Zhang, Aiping; Zhang, Hui
Abstract: In this study, the gelatin/nano-hydroxyapatite (n-HAP) composite nanofibrous films were fabricated by electrospinning. The gelatin/n-HAP mixtures in acetic aqueous solutions as the spinning dispersions showed a shear thinning behavior, and the apparent viscosity increased with the increasing n-HAP content. However, the average diameter of the gelatin nanofibers decreased from 516 to 510, 458 and 403 nm after the addition of 10%, 25% and 50% n-HAP, due to the decreased entanglement density. The EDS and TEM analysis indicated that n-HAP was uniformly dispersed within the nanofibers. As indicated by the FTIR results, the hydrogen bonding formed between gelatin and n-HAP resulted in the conformational transition of gelatin from β-sheet to turns. The water contact angle and XPS analysis suggested that the incorporation of n-HAP favored the wettability of the electrospun nanofibrous films, which was ascribed to the rough fiber surface and higher ratio of polar groups on the surface. The incorporation of 10% n-HAP did not affect the mechanical strength significantly, but the higher ratios of n-HAP led to the brittle and fragile property of the electrospun films. In addition, the water barrier property of the gelatin nanofibrous film was significantly improved by the addition of n-HAP. These results suggest that the surface wettability, mechanical strength and water barrier property of the electrospun gelatin nanofibrous films may be tuned by the incorporation of nano-hydroxyapatite. Graphical abstract: Image 1 Highlights: Addition of nano-hydroxyapatite (n-HAP) decreased the average diameter of the gelatin nanofibers. The β-sheet to turns conformational transition of gelatin resulted in a more compact structure of the nanofibers. The incorporation of n-HAP deteriorated the mechanical property of the nanofibrous film. The water vapor barrier property was significantly improved by the incorporation of n-HAP.